A case report: retigabine induced oral mucosal dyspigmentation of the hard palate. Issue 1 (December 2015) - Beacher, Nicholas; Brodie, Martin; Goodall, Christine
Abstract Background Dyspigmentation of the oral mucosa has a multitude of aetiological causes. Retigabine, a new antiepileptic drug, has the potential side effect of inducing a blue/purple pigmentation of the oral mucosa in addition to the skin, lips, nails and retina of the eyes. This article presents a unique case of dyspigmentation present in the oral mucosa of the hard palate which has previously been unreported in the dental literature. Case presentation A 70 year old white male presented to a secondary care oral surgery department with an unusual asymptomatic pigmented lesion present in the hard palate of the oral cavity. The pigmentation was remarkable for its distinct blue/purple colouration which was associated with a similar discolouration of the nail beds of the hands. This is believed to be a side effect of the anti-epileptic medication retigabine. Conclusion The dental profession and wider healthcare community should be made fully aware of the potential side effect of oral dyspigmentation associated with the novel anti-epileptic medication retigabine. Enhanced knowledge of the causative role of retigabine in dyspigementation of the oral mucosa will allow the practitioner to make an appropriate diagnosis. As far the authors are aware this is reaction is unreported in the dental literature and should be disseminated to the wider oral health professional's community.